2016
DOI: 10.7554/elife.15718
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt receptor complex activates a pathogenic type III secretion system

Abstract: Bile is an important component of the human gastrointestinal tract with an essential role in food absorption and antimicrobial activities. Enteric bacterial pathogens have developed strategies to sense bile as an environmental cue to regulate virulence genes during infection. We discovered that Vibrio parahaemolyticus VtrC, along with VtrA and VtrB, are required for activating the virulence type III secretion system 2 in response to bile salts. The VtrA/VtrC complex activates VtrB in the presence of bile salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 64 publications
(90 reference statements)
2
124
0
Order By: Relevance
“…Oligomerization of the N‐terminal DNA‐binding domain of VtrA enhances its DNA‐binding activity, thus probably facilitating the transcriptional regulatory activity of VtrA. V. parahaemolyticus T3SS2 regulator C (VtrC), a protein that is cotranscribed with VtrA, is also required for the transcriptional activation of the genes that encode T3SS2 . VtrC forms a complex with the C‐terminal domain of VtrA (VtrA/VtrC), which might stabilize VtrA in V. parahaemolyticus .…”
Section: Regulation Of T3ss2 Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligomerization of the N‐terminal DNA‐binding domain of VtrA enhances its DNA‐binding activity, thus probably facilitating the transcriptional regulatory activity of VtrA. V. parahaemolyticus T3SS2 regulator C (VtrC), a protein that is cotranscribed with VtrA, is also required for the transcriptional activation of the genes that encode T3SS2 . VtrC forms a complex with the C‐terminal domain of VtrA (VtrA/VtrC), which might stabilize VtrA in V. parahaemolyticus .…”
Section: Regulation Of T3ss2 Gene Expressionmentioning
confidence: 99%
“…Instead, bile induces VtrA oligomerization, causing enhanced binding of VtrA to the promoter region of vtrB . Cocrystallization of the periplasmic domain complex formed by VtrA and VtrC in the presence of taurodeoxycholate revealed that eight β‐strands of VtrC and one β‐strand of VtrA form a β‐barrel with a hydrophobic inner chamber that binds taurodeoxycholate . Although it is uncertain how the binding of bile acids to VtrA/VtrC affects the transcriptional regulatory activity of VtrA, these findings suggest that VtrA/VtrC senses bile, leading to the activation of the DNA‐binding domain of VtrA, probably through its oligomerization.…”
Section: Host‐derived Inducers For T3ss2 Gene Expressionmentioning
confidence: 99%
“…Analysis of the crystal structure of the periplasmic domains of the VtrA/VtrC heterodimer revealed that VtrA and VtrC form a protein complex on the surface of the outer membrane creating a barrel‐like structure that binds to bile salts and induces V . parahaemolyticus to secrete toxins (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Growth in the presence of bile salts allowed for induction of T3SS2 [11, 12]. Mammalian host cells were subsequently infected with CAB2 strains at a multiplicity of infection (MOI) of 10 using culture medium devoid of antibiotics (infection medium).…”
Section: Methodsmentioning
confidence: 99%